APLIKASI E-KATALOG PRODUK REPAUSE CLOTHING DENGAN FRAMEWORK CODEIGNITER BERBASIS WEB MOBILE - ARWAN NUGRAHA, 12.01.53.0076 (Information Technology and Telematics, 2017)
ABSTRACTElectronic catalogs (E-catalog) is an application that was built in an effort to categorize clothing products by category. Categorization is a cognitive process to classify objects and events into certain categories is meaningful. E-Catalog is an electronic information system that contains the list, type and price of a particular item. E-catalog is part of the marketing strategy, in order to reach customers and potential customers properly, then the E-catalog must be made on the appropriate digital media. Services E-Catalog Products Repause Clothing can be opened via the mobile web so that customers can access via desktop or smartphone. E-catalog is designed using CodeIgniter Framework. CodeIgniter is one of the many frameworks that use the concept of MVC (model, view, controller). Framework provides class libraries and helpers are very useful in creating a mobile web application. The results of this research is the application of the E-catalog of products repause clothing web-based mobile Guang Yu Book Store clothing products.Keywords: E-Catalog, CodeIgniter, Bootstrap, PHP, MySQLABSTRAKElektronik katalog (E-katalog) merupakan aplikasi yang di bangun dalam upaya  mengkategorikan suatu produk clothing sesuai dengan kategorinya.Kategorisasi adalah suatu proses kognitif untuk mengklasifikasikan objek-objek dan peristiwa ke dalam kategori-kategori tertentu yang bermakna. E-Katalog adalah sistem informasi elektronik yang memuat daftar, jenis, dan harga barang tertentu. E-katalog merupakan bagian dari strategi pemasaran, agar dapat menyentuh pelanggan serta calon pelanggan secara tepat, maka E-katalog harus dibuat pada media digital yang tepat. Layanan E-katalog Produk Repause Clothing dapat dibuka melalui web mobile sehingga pelanggan dapat mengaksesnya melalui dekstop maupun smartphone. E-katalog ini dirancang mengunakan Framework Codeigniter. Codeigniter adalah salah satu dari sekian banyak framework yang menggunakan konsep MVC (model, view, controller). Framework menyediakan class library dan helpers yang berguna dalam pembuatan sebuah aplikasi web mobile. Hasil dari penelitian ini adalah aplikasi E-katalog produk repause clothing berbasis web mobile yang beisi produk-produk clothing.Kata kunci : E-Katalog,Codeigniter,Bootstrap, PHP, MySQL